Detection of the risk of adenocarcinoma in Barrett's esophagus by means of tumor markers (p53 and ki67) - Trakal, Esteban (2010)
The rising incidence of adenocarcinoma in Barrett's esophagus has intensified the research into methods of early recognition of cancer risk, detecting cytological and architectural changes (dysplasia) or using biomarkers as predictive tests. The aim of this paper is to evaluate the involvement of two tumor markers: p53 (tumor suppressor gene) and Ki67 (proliferation marker), by means of immunohistochemical analysis with monoclonal antibodies designed for the specific localization of p53 and Ki67 antigens, in esophageal biopsies with columnar metaplasia of patients with and without dysplasia and adenocarcinoma, and to anticipate which ones are liable to suffer it in the future. Both markers were positive in all intestinal metaplasia patients with high-grade dysplasia and adenocarcinoma, and even in some cases with low grade or without dysplasia. In contrast, in those who have gastric metaplasia, tumor markers were negative. Expression of biomarkers next to dysplasia reduces interobserver variation. Patients with these abnormalities have to be included into a surveillance protocol.